PENGARUH KUOTA TERHADAP DAFTAR TUNGGU NAIK HAJI DI KOTA PADANG - JAPERI JAPERI (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The theme of the research is hajj management. The purpose of research is: to determine the effect of quota on waiting list hajj. This study is a literature study. Place of study is in Padang city, West Sumatera. The results of the study were: the very limited number of quotas had an effect on the Haj waiting list.